2009
DOI: 10.1111/j.1467-8667.2009.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Chloride Concentration Effect on Reinforcement Corrosion

Abstract: The corrosion of reinforcement is one of the major causes of deterioration of reinforced concrete (RC) structures, considerably affecting their durability and reliability. The rate of reinforcement corrosion is governed by, among other factors, the presence of chlorides on the surface of the steel. The assessment of such deteriorating effects necessitates the development of relevant models and the utilization of advanced simulation techniques to enable the probabilistic analysis of concrete structures. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Such significant variations explain the necessity of considering both temporal and spatial uncertainties in the investigation of deterioration processes. More recent studies have demonstrated the advantages of incorporating the variability of the involved parameters into the predictive models (e.g., Sudret et al, ; Vorechovska et al, ; Choi and Seo, ; Zhang and Gao, ; Cusson et al, ). These studies indicate how the estimation of the likelihood and extent of corrosion damage can be improved when the influential parameters are treated as random variables.…”
Section: Introductionmentioning
confidence: 99%
“…Such significant variations explain the necessity of considering both temporal and spatial uncertainties in the investigation of deterioration processes. More recent studies have demonstrated the advantages of incorporating the variability of the involved parameters into the predictive models (e.g., Sudret et al, ; Vorechovska et al, ; Choi and Seo, ; Zhang and Gao, ; Cusson et al, ). These studies indicate how the estimation of the likelihood and extent of corrosion damage can be improved when the influential parameters are treated as random variables.…”
Section: Introductionmentioning
confidence: 99%
“…Models for carbonation , chloride ingress , reinforcement corrosion as well as for acid and frost attack are provided. Recently, some new issues have been studied and integrated into FReET‐D, namely models for deterioration due to biogenic sulfuric acid and models for synergy of concrete carbonation or chloride and mechanical load effects .…”
Section: Degradation Modelingmentioning
confidence: 99%
“…The Models for carbonation [22], chloride ingress [17,23,24], reinforcement corrosion [25] as well as for acid and frost attack are provided.…”
Section: Degradation Modelingmentioning
confidence: 99%
“…Durability of concrete exposed to aggressive agents has been a worldwide research topic in recent decades [1][2][3][4][5]. Such agents are chloride ions that reduce the long-term durability of reinforced concrete (RC) structures during their service lifetime.…”
Section: Introductionmentioning
confidence: 99%